COLLIOD BLOOD SUBSTITUTES – EMULGENTS OF LIPID GLOBULES IN SEVERE CONCURRENT TRAUMA - A. Yu. Yakovlev; A. A. Pevnev; M. S. Belous; D. V. Ryabikov; S. I. Chistyakov (Вестник анестезиологии и реаниматологии)
.